2021
DOI: 10.1136/bmjopen-2021-050377
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the factors and the key indicators that identify doctors at risk of complaints, malpractice claims or impaired performance

Abstract: ObjectiveTo identify the risk factors associated with complaints, malpractice claims and impaired performance in medical practitioners.DesignSystematic review.Data sourcesOvid-Medline, Ovid Embase, Scopus and Cochrane Central Register of Controlled Trials were searched from 2011 until March 2020. Reference lists and Google were also handsearched.ResultsSixty-seven peer-reviewed papers and three grey literature publications from 2011 to March 2020 were reviewed by pairs of independent reviewers. Twenty-three ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…Personal factors are more likely to require remediation when learners are older [ 102 , 117 , 118 ], had reported character failings [ 119 ], required remediation in the past [ 120 ], learners who required more time to complete medical school [ 121 ], had more re-examinations in the past [ 121 ] and previous lapses in professionalism in medical school [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Personal factors are more likely to require remediation when learners are older [ 102 , 117 , 118 ], had reported character failings [ 119 ], required remediation in the past [ 120 ], learners who required more time to complete medical school [ 121 ], had more re-examinations in the past [ 121 ] and previous lapses in professionalism in medical school [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…Program related factors predisposing to professional lapses and the need for remediation [ 66 ] include high workload [ 84 , 112 , 118 ], chronic fatigue, sleep deprivation, stress and overwork [ 84 ], a “culture of recurrent assessment and unsupportive teaching environments” [ 74 ] and changing placements which requires learners to adapt to new environments and form new relationships [ 74 ]. Frameworks for Remediation …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that risk factors in healthcare settings are multifactorial and interdependent. 2 Therefore, adopting an organizational or system theory might advance the understanding of related topics. 40 The present study is not exempt from limitations.…”
Section: Discussionmentioning
confidence: 99%
“…One conservative case-based model estimated a $4.6 billion each year in added health care cost from burnout related to physician turnover and reduced clinical hours 5 . Additional consequences of physician burnout include medical errors, staff turnover, and decreased patient satisfaction 6,7 …”
mentioning
confidence: 99%
“…5 Additional consequences of physician burnout include medical errors, staff turnover, and decreased patient satisfaction. 6,7 Many contributing factors to burnout have been identified, with 80% categorized as system-related, such as loss of autonomy, use of an electronic health record, and excessive workload, the latter related to increased time on patient-related tasks and administrative work outside of clinical hours. [8][9][10][11] Additional factors contributing to burnout include longer hours at work and more nights on call.…”
mentioning
confidence: 99%